Another origin of yield drop behavior in sapphire deformed via basal slip: Recombination of climb-dissociated partial dislocations. (September 2017) - Nakamura, Atsutomo; Matsunaga, Katsuyuki; Tochigi, Eita; Shibata, Naoya; Ikuhara, Yuichi; Lagerlöf, K. Peter D.
Abstract: It is demonstrated from repeated loading-unloading high-temperature deformation tests of sapphire crystals deformed via basal slip that the deformation stresses go back to the same level as just before unloading after a small yield drop is observed during the re-loading process. This phenomenon suggests that basal dislocations that work as primary slip system regain the ability of glide motion even after they are dissociated into two partial dislocations via self-climb. That is, the climb-dissociated partials in basal dislocations introduced by previous deformation recombine onto the same basal plane so that they can glide again, resulting in the yield drop. Graphical abstract: